FACTORS AFFECTING PROFITABILITY IN BANKING ENTERPRISES - Nelson, Catheryn Iona; Ester, Ester; Jeninfer, Jeninfer; Viorene, Viorene (Universitas Bunda Mulia, 2024)
Background: Banking companies were chosen as subjects for this study because banking companies experienced an increase in profits along with stronger profitability ratios, so banking companies were considered very prospective for investors.Objective: This study aims to determine the effect of company size, leverage, as well as public share ownership on profitability in banking companies listed on the Indonesia Stock Exchange in 2020 - 2022Research Method: The sampling technique in this study used a purposive sampling technique with a sample of 30 banking companies. This study used linear regression data analysis with the help of SPSS to test the hypothesis, with a descriptive type of research.Research Results: The results of this study show that company size has a positive influence on profitability, while leverage has a negative influence on profitability. On the other hand, public shareholding does not affect profitability.Originality/Novelty of Research: Analyzing the latest regulations regarding free float for companies on the IDX, especially in the banking subsector.